STRATEGI PROMOSI DALAM MENINGKATKAN VOLUME PENJUALAN MOBIL MITSUBISHI STUDI PADA PT. LAUTAN BERLIAN UTAMA MOTOR LAHAT - Darsih Darsih (JEM Jurnal Ekonomi dan Manajemen, 2021)
The promotion has a very important role in the successful sale of company products and services, including companies engaged in the sale of automotive products. This study aims to determine the promotion problems faced by the company and solutions to solving problems faced in the promotion. Data analysis with a qualitative approach, with a SWOT analysis approach, with the object of study at PT. Lahat Motors Ultimate Diamond Ocean. The results of the study show that the problem faced by the company is the decline in sales volume of Mitsubishi cars, this is due to internal and external factors. In addition, promotional activities have not been optimal due to a lack of expertise from human resources who occupy marketing positions so that promotional activities have not reached the target and sales targets are not being achieved.